TRANSESTERIFICATION OF PALM OIL USING THE TiO2/nano-MONMORILLORITE (nano-MMT) COMPOSITE CATALYST FROM ACEH TAMIANG BENTONITE IN THE PRODUCTION OF BIODIESEL - Fadlly, Teuku Andi; Nila, Ida Ratna; Sari, Nirmala (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Transesterification of palm oil using a TiO2/nano-Monmorillorite (nano-MMT) composite catalyst from Aceh Tamiang bentonite in Biodiesel production has been carried out. Biodiesel is bioenergy obtained from vegetable oils, animal fats, microorganisms, and plants. This is alternative energy to replace fossil fuels, especially diesel oil. Biodiesel is proven to be more environmentally friendly in reducing hydrocarbon and sulfur emissions. In this study, TiO2 will be composited with nano-MMT using the solid-state method and analyzed using XRD. Both of these materials are used as catalysts for biodiesel production. The transesterification process will be used in the production of biodiesel, where the molar ratio of palm oil to methanol is 1:12. TiO2/nano-MMT composite catalyst will be varied (2 and 4 grams). Biodiesel samples will be analyzed using GC-MS. The results obtained show that the TiO2/nano-MMT composite catalyst from Aceh Tamiang bentonite can convert Fatty Acid Methyl Ester (FAME) from palm oil. The 2 grams of the composite catalyst produced biodiesel of 89.38% and 4 grams of 64.88%.